Factors influencing employee engagement : a case survey at Majlis Agama Islam dan Adat Istiadat Melayu Kelantan / Nor Akhmar Alias - Alias, Nor Akhmar (2019)
The purpose of this study to examine the relationship between independent variables (IV); Internal communication, employee attitude and skills and knowledge on dependent variable (DV); employee engagement. Employees at Majlis Agama Islam dan Adat Istiadat Melayu Kelantan were taken as the respondents in this study. Self- administered questionnaire used for collection of data. 175 questionnaires were distributed among the above mentioned organization and 175 were returned, so the response rate was 100%. The results conclude that there is significant relationship between internal communication and employee attitude on employee engagement. Meanwhile, there is no significant relationship between skills and knowledge and employee engagement. Several recommendations were provided in this study for the organization in promoting employees’ engagement as well as recommendation for the future.